PENGARUH BOARD GENDER DIVERSITY, OWNERSHIP STRUCTURE DAN DIVIDEND PAYOUT RATIO TERHADAP FINANCIAL PERFORMANCE - Andina Eka Prihertanti (2022)
This study aims to determine the effect of Board Gender Diversity, Ownership Structure and Dividend Payout Ratio on Financial Performance. The independent variable in this study was Board Gender Diversity measured by dummy with a weight of 1 for companies that have women on board structure. Ownership Structure measured by ratio of shares owned by government and Dividend Payout Ratio measured by dividend per share divided by earning per share. The population in this study are all state owned enterprises listed on the Indonesia Stock Exchange (IDX) with an observation period of 5 years 2017 - 2021 using a purposive sampling methode and the total sample obtained is 6 sample companies per year so that total sample was 30 samples. The results of this study indicate that board gender diversity has significant negative effect on financial performance, ownership structure has no significant effect on financial performance and dividend payout ratio has a significant negative effect on financial performance.